Pembangunan Desa Laweyan Melalui UMKM Kreatif Unggulan - Nisa, Fauzatul Laily; Fadil, Cholid (Yayasan Daarul Huda Kruengmane, 2024)
Village development is an important aspect in encouraging economic growth and community welfare in Indonesia. This research aims to analyze Laweyan village development efforts through superior creative MSMEs and their impact on economic growth and welfare of local communities with a research focus on mushroom farmers and bamboo woven craftsmen. The location is in Laweyan Village, Sumberasih District, Probolinggo Regency. The method used is PAR (Participatory Action Research) and other approaches such as training and mentoring. Through the profile of superior creative MSMEs which include mushroom farmers and woven craftsmen, Laweyan Village can take advantage of its cultural riches and economic potential. Top creative MSMEs are very important for the growth of Laweyan Village. The results of this research show that the people in Laweyan Village optimize the resources and potential of the village so as to produce superior creative MSMEs which can ultimately strengthen cultural identity, improve the quality of life of the community, and attract tourists to visit this village. However, limited access to funds, marketing and distribution, lack of skills and creativity, strengthening networks and collaboration, and preserving intellectual property rights. Apart from that, the existence of superior creative MSMEs plays an important role in village development, namely in local economic growth, increasing community income, social development, cultural preservation, as well as tourism and village promotion.